Mango cultivars behavior in relation to fusarium subglutinans - Zaccaro, R. P. [UNESP]; Donadio, L. C. [UNESP]; Lemos, E. G M [UNESP] (My University, 2004)
The mango malformation, caused by the fungus Fusarium subglutinans Wollenweb & Reinking, is probably one of the diseases that causes more damages in the mangoes production in Brazil and other producing countries. This fungus was isolated of a Tommy Atkins plant with advanced symptoms of malformation, purified and prepared to be inoculated in 15 cultivars of national and imported mangoes. Initially, 10 cultivars had been inoculated in July/2000: Bourbon IAC - 100, Coração de Boi, Keitt, Parvin, Primor de Amoreira, Sensation, Smith, Surpresa, Tommy Atkins and Van Dyke. Another group was inoculated in December/2000, on the cultivars: Adams, Bhadauran, Palmer, Princesa and Zill, and with others cultivars Primor de Amoreira, Sensation and Tommy Atkins, that were inoculated in the first time, with the purpose to compare the two times of inoculation. Throughout the evaluated data at the two times of inoculation, after 11 months of evaluation, were maden the analysis of the variance in function of the involved sources of variation and the test of Duncan to compare the averages of inoculated cultivars. With the results obtained, the cultivars Bhadauran, Palmer, Parvin, Sensation, Van Dyke and Zill presents less percentage of plants with malformation symptoms or less progression of symptoms in relation to the others inoculated cultivars, under protected environmental conditions, where the assays were carried out.
Keywords: Inoculation; Malformation; Mangifera indica L